Issues in reading comprehension: A case of an Indonesian bilingual dyslexic student - Angkita Wasito Kirana (Universitas Pendidikan Indonesia, 2022)
The complexity of a reading process often becomes an obstacle for students with dyslexia, particularly those studying in bilingual schools. To date, few studies discuss the Indonesian-English bilingual dyslexic student’s reading processes when they encounter reading texts in both languages they are acquiring. This study aimed to investigate the tendency of a dyslexic student’s reading comprehension in reading texts in the Indonesian and English language. This was done by comparing the reading comprehension of a second-grade Indonesian dyslexic participant (age=9) and four control participants. Two sets of reading instruments, written in the Indonesian language. The keywords used in each language were taken from participants’ textbooks. There were two types of sentences in the reading instrument; highly contextual sentences and sentences which is in accordance with participants’ background knowledge. After reading each sentence, they were asked to answer comprehension questions about each keyword. The scoring was based on their answer accuracy. The results were analyzed based on the reading comprehension theories proposed by Kintsch and Rawson (2005). The results showed that the two groups used different strategies to comprehend the text but the dyslexic participant's reading performance was lower than the control participants' performance in both languages. The results suggested that the dyslexic participant’s reliance on his background knowledge and lack of ability in retrieving appropriate keywords were the sources of his poor reading performance. Practices to improve skills in retrieving background knowledge and utilizing working memory span are suggested.